2018
DOI: 10.1631/jzus.b1700191
|View full text |Cite
|
Sign up to set email alerts
|

Role of jasmonic acid in improving tolerance of rapeseed (Brassica napus L.) to Cd toxicity

Abstract: Abstract:The well-known detrimental effects of cadmium (Cd) on plants are chloroplast destruction, photosynthetic pigment inhibition, imbalance of essential plant nutrients, and membrane damage. Jasmonic acid (JA) is an alleviator against different stresses such as salinity and drought. However, the functional attributes of JA in plants such as the interactive effects of JA application and Cd on rapeseed in response to heavy metal stress remain unclear. JA at 50 µmol/L was observed in literature to have senesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…These hormones modulate the antioxidative defense system of plants, resulting in reduction of the oxidative stress under abiotic stress conditions. Earlier studies have also reported the protective role of JA in Brassica plants under different abiotic stress conditions like salt ( Kaur et al, 2017 ), cadmium ( Ali et al, 2018 ), arsenic ( Farooq et al, 2016 ), and lead ( Bali et al, 2018a ). JA also regulates the plant defense system under herbicide toxicity by modulating the biochemical and physiological responses of tobacco plants ( Kaya and Doganlar, 2016 ).…”
Section: Introductionmentioning
confidence: 95%
“…These hormones modulate the antioxidative defense system of plants, resulting in reduction of the oxidative stress under abiotic stress conditions. Earlier studies have also reported the protective role of JA in Brassica plants under different abiotic stress conditions like salt ( Kaur et al, 2017 ), cadmium ( Ali et al, 2018 ), arsenic ( Farooq et al, 2016 ), and lead ( Bali et al, 2018a ). JA also regulates the plant defense system under herbicide toxicity by modulating the biochemical and physiological responses of tobacco plants ( Kaya and Doganlar, 2016 ).…”
Section: Introductionmentioning
confidence: 95%
“…Seed germination and seedling establishments are the two critical stages in plant growth. These stages are the most sensitive to environmental conditions including salinity [120]. Plants are usually seeded within the top layer of the soil which is more saline than lower layers [121].…”
Section: Alleviation Salinity Stress On Germination By Seed Primingmentioning
confidence: 99%
“…Nitric oxide (NO) regulates several plant growth and developmental activities, stress signalling molecules and stress responses, including salinity and the activation of antioxidant enzymes (superoxide dismutase (SOD), CAT, guaiacol peroxidase (GPX), ascorbate peroxidase (APX), and glutathione reductase (GR)), and triggers the expression of various redox-regulated genes that enhance germination and root growth under salinity stress (Gupta and Huang, 2014). Salinity stress mitigation by NO is due to its antioxidant functions, modulation of the ROS detoxification system (Mishra et al, 2011) associated with an increase in antioxidant enzymes, such as SOD, CAT, GPX, APX, and GR (Zhao et al, 2004;Ali et al, 2018), and suppression of malondialdehyde (MDA) production during lipid peroxidation (Nalousi et al, 2012). NO offers a force for Na + /H + exchange, providing the H + gradient to stimulate H + -ATPase (H + -PPase) and contributing to K + and Na + homeostasis (Zhang et al, 2006;Gupta and Huang, 2014).…”
Section: Biochemical Indicatorsmentioning
confidence: 99%